2021
DOI: 10.1177/08862605211037580
|View full text |Cite
|
Sign up to set email alerts
|

Parental Harsh Discipline and Migrant Children’s Anxiety in China: The Moderating Role of Parental Warmth and Gender

Abstract: The present study examined the moderating effects of both parents’ warmth in the relations between parental harsh discipline (psychological aggression and corporal punishment) and migrant children’s anxiety and parent and child gender differences in the moderating mechanism in Chinese society. This study used a sample of 477 elementary school-age children and both their parents in Chinese migrant families. We constructed a Structural Equation Model to explore the relation between parental harsh discipline (psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…37 However, there was no consistent conclusion with regard to the role of gender in the association between harsh discipline and anxiety. 38,39 Prior research revealed that internalizing behavior mediated the association between child maltreatment and externalizing behavior, while gender difference was found in this mediation model. 40 To best of our knowledge, no research has conducted to examine the sex difference in the mediation model regarding the impact of parental psychological aggression on phubbing via anxiety.…”
Section: Sex and Grade Differencesmentioning
confidence: 93%
See 1 more Smart Citation
“…37 However, there was no consistent conclusion with regard to the role of gender in the association between harsh discipline and anxiety. 38,39 Prior research revealed that internalizing behavior mediated the association between child maltreatment and externalizing behavior, while gender difference was found in this mediation model. 40 To best of our knowledge, no research has conducted to examine the sex difference in the mediation model regarding the impact of parental psychological aggression on phubbing via anxiety.…”
Section: Sex and Grade Differencesmentioning
confidence: 93%
“…Although the similar discipline methods adopted by parents for girls and boys, they may differ on the reaction to punishment [ 37 ]. However, there was no consistent conclusion with regard to the role of gender in the association between harsh discipline and anxiety [ 38 , 39 ]. Prior research revealed that internalizing behavior mediated the association between child maltreatment and externalizing behavior, while gender difference was found in this mediation model [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that parental harsh discipline and children's internalizing and externalizing problematic behavior may vary based on gender (Chang et al, 2003;Liu et al, 2022). According to the social role theory, society has distinct expectations on different genders, which are what make up gender roles (Eagly et al, 2000).…”
Section: Gender Differences In the Mediating Mechanismmentioning
confidence: 99%
“…Under the traditional Chinese view of parental harsh discipline, Chinese children may be less likely to view parental harsh discipline as rejection, and experience less anxiety. Nevertheless, in recent years, limited studies with Chinese families have shown that parental harsh discipline was associated with children's anxiety (Liu & Wang, 2020;Liu et al, 2022;, which suggested that even in the context of high acceptance of parental harsh discipline in China, children tend to be anxious after experiencing parental harsh discipline. Despite such progress, most research in this area in China is cross-sectional (Liu & Wang, 2020;Liu et al, 2022; M. , and little is known about the predictive effects of parental harsh discipline on Chinese children's anxiety.…”
Section: Parental Harsh Discipline and Children's Anxietymentioning
confidence: 99%
“…Nevertheless, in recent years, limited studies with Chinese families have shown that parental harsh discipline was associated with children's anxiety (Liu & Wang, 2020;Liu et al, 2022;, which suggested that even in the context of high acceptance of parental harsh discipline in China, children tend to be anxious after experiencing parental harsh discipline. Despite such progress, most research in this area in China is cross-sectional (Liu & Wang, 2020;Liu et al, 2022; M. , and little is known about the predictive effects of parental harsh discipline on Chinese children's anxiety. Therefore, to provide evidence for early prevention and intervention for children's anxiety, it is necessary to pay attention to the predictive effects across time.…”
Section: Parental Harsh Discipline and Children's Anxietymentioning
confidence: 99%